1980
DOI: 10.1002/cber.19801130529
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von Baicalin und einiger anderer Baicalein‐glycoside

Abstract: Die 6-und 7-O-~-o-Glucopyranoside 14 und 7 bzw . die 6-und 7-O-P-~-Glucopyranosiduronsauren 18 und 9 des Baicaleins (1) wurden hergestellt. 9 ist rnit Baicalin identisch, jedoch stimmte weder 14 mit Tetuin, noch 18 mit ,,Baicalein-6-glucuronid" aus Oroxylum indicum uberein. Synthesis of Baicalin and Some Other Baicalein Glycosides')The 6-and 7-O-~-o-glucopyranosides 14 and 7 and the 6-and 7-O-~-~-glucopyranosiduronic acids 18 and 9 of baicalein (1) have been synthesized. 9 was identical with baicalin but 14 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…The suspension was seeded with the product mixture, cooled in the ice bath, filtered, and washed with cold water. The product was dried in vacuo for 12 h at 40 °C to yield 650 mg (75%) of oroxin A ( 1 ) as a light yellow solid (mp 221–222°C, in lit 25 : 222–223 °C). 1 H NMR (400 MHz, DMSO- d 6 ): 12.57 (s, 1H), 8.59 (s, 1H), 8.08 (d, 2H, J = 8.0 Hz), 7.57–7.63 (m, 3H), 7.06 (s, 1H), 7.02 (s, 1H), 5.42 (d, 1H, J = 4.0 Hz), 5.16 (d, 1H, J = 4.0 Hz), 5.11 (d, 1H, J = 4.0 Hz), 5.02 (d, 1H, J = 8.0 Hz), 4.68 (t, 1H, J = 4.0 Hz), 3.74–3.78 (m, 1H), 3.48–3.52 (m, 2H), 3.18–3.24 (m, 1H).…”
Section: Methodsmentioning
confidence: 99%
“…The suspension was seeded with the product mixture, cooled in the ice bath, filtered, and washed with cold water. The product was dried in vacuo for 12 h at 40 °C to yield 650 mg (75%) of oroxin A ( 1 ) as a light yellow solid (mp 221–222°C, in lit 25 : 222–223 °C). 1 H NMR (400 MHz, DMSO- d 6 ): 12.57 (s, 1H), 8.59 (s, 1H), 8.08 (d, 2H, J = 8.0 Hz), 7.57–7.63 (m, 3H), 7.06 (s, 1H), 7.02 (s, 1H), 5.42 (d, 1H, J = 4.0 Hz), 5.16 (d, 1H, J = 4.0 Hz), 5.11 (d, 1H, J = 4.0 Hz), 5.02 (d, 1H, J = 8.0 Hz), 4.68 (t, 1H, J = 4.0 Hz), 3.74–3.78 (m, 1H), 3.48–3.52 (m, 2H), 3.18–3.24 (m, 1H).…”
Section: Methodsmentioning
confidence: 99%
“…In 1980, Mazey‐Vandor et al. reported the first total synthesis of baicalin ( 2 ) with the desired glycoside in a meager yield (44 %) [80] . In 2015, Y‐F Li et al.…”
Section: Natural Products and Their Derivatives With Activity Against Sars‐cov‐2mentioning
confidence: 99%
“…So far, only one total synthesis of baicalin was reported by Mazey-Vandor et al in 1980. 10 Two other studies reported the synthesis of baicalein, 11 that is, the aglycon of baicalin. In MazeyVandor's synthetic route, glucuronic bromide was used as the donor to form the critical glucuronic linkage, obtaining the desired glycoside in a low yield of 44%.…”
Section: Introductionmentioning
confidence: 99%
“…13 Collectively, these difficulties account for the low yielding glycosylation in MazeyVandor's work. 10 In this study, we have developed an efficient synthetic route for obtaining baicalin and its analogs from cheap commercially available starting materials. This goal is in line with our continuous efforts in the synthesis of bioactive flavonoid glycosides.…”
Section: Introductionmentioning
confidence: 99%